The making of riveted joint by dimpling process to increase the strength / Mohd Zawahir Che Omar - Che Omar, Mohd Zawahir (Faculty of Mechanical Engineering, 2003)
The thesis “Riveted Joint by Using Hot Dimpling Process to Increase the Strength” is a part of the sheet metal repair for an aircraft structure. In association with this, he should know how to make the riveted joint. Such as rivet selection, materials want to use, tool required and rivet layout. In addition, the aim and objective of this thesis, in order to increase the strength of riveted joint. In particular, the riveted joint make with the “Dimpling Process”. How we want to know the strength? Make a sample and test. Where the tests that occupy are tensile strength, metallurgical deformation and rivet layout. On the finishing point of the test, observation and discussions about the test specimen will be liability. With some of the design riveted joint. For the conclusion of this thesis will suggest to work place for further studies.